The Effect of Predict, Observe, And Explain (POE) Learning Model on Self Efficacy and Student Learning Outcomes on Basic Chemical Law Material - Wahyuni, Tutik Sri; Rakhmawati, Alfiana Eka; Irawati, Ratna Kartika (Universitas Pendidikan Mandalika, 2024)
The purpose of this study was to describe the effect of POE (Predict, Observe, and Explain) learning model on: 1) self efficacy, 2) student learning outcomes, and 3) self efficacy and student learning outcomes on basic laws of chemistry. This study used a quantitative approach with an experimental design of the quasi-experiment type, and with a non-equivalent control group design. The population in this study were class X students of SMAN 1 Ngunut, while the samples were class X-E as the experimental class and class X-F as the control class with the sampling technique was purposive sampling. The research instrument in the form of a questionnaire was used to measure student self-efficacy and test questions were used to measure student learning outcomes. Data analysis used prerequisite tests (normality test and homogeneity test), and hypothesis tests use independent sample t-test and manova test. The results showed that: 1) there is an effect of the POE learning model on self-efficacy with a sig value. (2-tailed) 0.000 <0.05, 2) there is an effect of the POE learning model on student learning outcomes with a sig value. (2-tailed) 0.000 <0.05, and 3) there is an effect of the POE learning model on self efficacy and student learning outcomes on the material of basic laws of chemistry with a sig value. (2-tailed) 0.000 <0.05.